1995
DOI: 10.1038/sj.npp.1380272
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Glucose Utilization in Polysubstance Abuse

Abstract: Regional cerebral glucose metabolism in subjects with histories of polysubstance abuse was compared to that in control subjects who were drawn from the same community. The substance abuse group showed lower absolute metabolic rates for glucose in lateral occipital gyrus and higher normalized metabolic rates in temporal and frontal areas, including orbitofrontal cortex. It is suggested that some patterns of brain function associated with polysubstance abuse may represent consequences of drug exposure, or they c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Priming dose effects (‘drug probing’) . Six studies measured the effect of placebo and a single dose of the drug of preference (or a closely related drug; Stapleton et al , 1995; Volkow et al , 1996, 1999 a , 2003 a ; Sell et al , 2000; Adinoff et al , 2001). All but one (Adinoff et al , 2003 a ) demonstrated orbitofrontal cortex activation in response to drug administration.…”
Section: Resultsmentioning
confidence: 99%
“…Priming dose effects (‘drug probing’) . Six studies measured the effect of placebo and a single dose of the drug of preference (or a closely related drug; Stapleton et al , 1995; Volkow et al , 1996, 1999 a , 2003 a ; Sell et al , 2000; Adinoff et al , 2001). All but one (Adinoff et al , 2003 a ) demonstrated orbitofrontal cortex activation in response to drug administration.…”
Section: Resultsmentioning
confidence: 99%
“…Neuroimaging studies provide evidence of functional (5,6,7,8) and structural abnormalities in orbitofrontal cortex (OFC) in substance dependence. Liu et al found smaller prefrontal, but not temporal cortex, in poly-substance abusers compared to controls (9).…”
Section: Introductionmentioning
confidence: 99%
“…The Nonplanning and the Attentional subscales are thought to be associated to impulsive choice or decision making (Patton et al, 1995; Winstanley et al, 2006), and from the neurobiological point of view, impulsive decision making has been linked to functional deficits in the orbitofrontal and the ventromedial PFC, including the frontal pole (see Winstanley et al, 2006, for discussion). This background is relevant because these brain regions have also been associated, at least in part, to neurobiological deficits underlying addiction (London et al, 2000; Stapleton et al, 1995; Volkow et al, 1992; Volkow & Fowler, 2000). Regarding behavioral tests, there was also a significant improvement in the Error Commission subscale of the CPT, a neurocognitive test associated to motor impulsivity (Dalley et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In chronic cocaine-dependent individuals, there is consistent evidence of structural (Tanabe et al, 2009) and functional abnormalities in prefrontal regions, especially in orbitofrontal areas (London et al, 2000; Stapleton et al, 1995; Volkow et al, 1992; Volkow & Fowler, 2000). Increased activity of the striatum and limbic regions relative to prefrontal areas (Hu et al, 2015) has also been reported.…”
Section: Introductionmentioning
confidence: 97%